Derivation of shear enhancement factor β used in FprEN1992 to calculate design shear force at corner columns of flat slabs. (May 2023) - Abu-Salma, Deema; Vollum, Robert L.; Macorini, Lorenzo
Abstract: The next generation of Eurocode 2 (FprEN 1992) adopts a closed form version of the Critical Shear Crack Theory (CSCT) for punching shear design. The code accounts for loading eccentricity by multiplying the design shear force by a coefficient β . The paper describes the derivation of the expression adopted in FprEN 1992 for β at corner columns of flat slabs. The proposed formula is validated for normal size columns, with maximum side length less than 3 d, where d is the slab mean effective depth, and non-square columns with long side greater than 3 d . Due to the absence of experimental data on punching resistance at non-square corner columns, the derived formula is validated for such columns using NLFEA with 3-D solid elements. Comparisons are also made with punching resistances determined using the classic CSCT in which punching resistance is explicitly related to slab rotation relative to the support. The closed form CSCT is shown to predict punching shear resistance well, when used in conjunction with the proposed β factor.